Subjective Well-Being dan Kecenderungan Narsisme Pada Individu Dewasa (SUKMA : Jurnal Penelitian Psikologi, 2020)
This research aims to know the relationship between subjective well-being with the tendency of narcissism in adulthood. The hypothesis proposed in this study was that there was a negative link between subjective well-being with a tendency to narcissism. It means that the higher subjective well-being one then the lower the tendency of Narcissism. The population in this research is an adult who has a social media account. While the sample in this study amounted to 94 adult respondents aged between 20-40 years. The sampling technique is carried out in a purposive sample. The method of collecting data in this study used a tendency scale of narcissism and a subjective well-being scale. The method of analysis used is the correlation technique of Spearman rho. Data analysis results show the magnitude of the correlation coefficient between the subjective well-being variable with the tendency variable narcissism of -0.283 and P = 0.006 (P ? 0.05). The results showed a significant and negative relationship between subjective well-being with the tendency of narcissism in adults with a percentage of 6,7% in subjective well-being while the remaining of 93,3% was influenced by variables other.Penelitian ini bertujuan untuk mengetahui hubungan antara subjective well-being dengan kecenderungan narsisme pada individu dewasa. Hipotesis yang diajukan dalam penelitian ini adalah ada hubungan negatif antara subjective well-being dengan kecenderungan narsisme. Artinya semakin tingginsubjective well-being seseorang maka akan semakin rendah kecenderungannnarsismenya. Populasi dalam penelitian ini adalah individu dewasa yang memiliki akun media sosial. Sedangkan sample dalam penelitian ini berjumlah 94 responden individu dewasa berusia antara 20-40 tahun. Teknik pengambilan sample dilakukan dengan cara purposive sampling. Metode pengumpulan data dalam penelitian ini menggunakan skala kecenderungan narsisme dan skala subjective well-being. Metode analisis yang digunakan ialahnteknik korelasi spearman rho. Hasil analisa data menunjukkan besarnya koefisien korelasi antara variabel subjective well-being dengan variabel kecenderungan narsisme sebesar -0,283 dan p= 0,006 (p?0,05). Hasil tersebut menunjukkan adanya hubungan yang negatif dannsignifikan antara subjective well-being dengan kecenderungan narsisme pada individu dewasa dengan prosentase sebesar 6,7% pada subjective well-being sedangkan sisanya sebesar 93,3% dipengaruhi oleh variabel lain.  Kata kunci: subjective well-being, kecenderungan narsisme